MYTHS AND ARCHETYPES IN ANCIENT IRAN AND ITS IMPACT ON POWER - Moradi, Seyed; Khorramshad, Mohammad (PEOPLE: International Journal of Social Sciences, 2017)
History of Iran has been the origin of different mythologies. Politics has been also related to the situation and power has never been far from myth. Myths have sustained and reproduced the collective archetypes of mythology; so that they have never been lost in history and remained in unconscious collective and historical memory. Ancient texts, including Avesta, have both been influenced by myths and produced new myths. Archetypes of hero, wise old man, anima and animus and etc. affected political affairs in Iran and continued during different historical periods and have played a role in its evolutions. Today, according the same trend, politics and identity are affected by mythology, which has lingered on through the collective memory. It seems that the situation has been more severe in Iran.